Negotiating Respect : Pentecostalism, Masculinity, and the Politics of Spiritual Authority in the Dominican Republic - Thornton, Brendan Jamal (Book collections on Project MUSE., 2016)
In his study of a barrio of Villa Altagracia, Brendan Thornton examines the appeal of Pentecostalism by showing how conversion inverts traditional models of legitimacy, transforming narratives of spiritual authority that, once based on virtue, are now based on redemption.